PROFESSIONAL STANDARDS FOR EDUCATIONAL MANAGERS: ANALISING THE EXPERIENCE OF COUNTRIES WITH DIFFERENT SOCIO-ECONOMIC DEVELOPMENT WITH THE VIEW OF ITS POSSIBLE USE IN UKRAINE - Zadorozhna-Kniahnytska, Lenina; Netreba, Marina; Holiuk, Oksana; Zolotko, Julia; Khadzhinova, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Professional standards for educational managers establish the compliance of a person with the professional requirements; therefore, it is important to study them in order to develop the content of university training programs for school principals. The aim of the present research is to examine the experience of standardization of educational managers’ professional activity in the countries of different socio-economic development and various degrees of participation in the global educational integration processes, as well as to highlight the possible use of best practices to develop and implement the most effective university training programs for educational managers. We conducted the study during 2018 – 2020 according to the methodology of the aspect analysis, having distinguished two aspects: functional and behavioural. We analysed the professional standards within the framework of regional clusters taking as a basis the mutual convergence and interaction of their educational systems, namely regions that are the generators of integration processes; regions that respond positively to integration processes but do not initiate them; regions that are inert to the integration of educational processes. Furthermore, we chose a few countries from each cluster, which adopted the standards at the state level or at the level of individual administrative units within a particular country. The results of the analysis made it possible to identify general and special trends, peculiar to certain groups of countries. The results obtained within the framework of the study made it possible for us to develop the construct of the standard that takes into account the particular features of socio-economic development of Ukraine.